Minimun physical requirements of the physical workers of an electric supply company by way of work-specific physical assessments. - Kruger, P.E. (Pieter Ernst) (University of Pretoria, 2013)
Dissertation (MA(Human Movement Science))--University of Pretoria, 2003.